Progress in Difluoroalkylation of Organic Substrates by Visible Light Photoredox Catalysis - Lemos, Agostinho (Adv Synth Catal, 2019)
The selective incorporation of fluorinated motifs, in particular CF(2)FG (FG=a functional group) and CF(2)H groups, into organic compounds has attrracted increasing attention since organofluorine molecules are of the utmost importance in the areas of nuclear imaging, pharmaceutical, agrochemical, and material sciences. A variety of synthetic approaches has been employed in late‐stage difluoroalkylation reactions. Visible light photoredox catalysis for the production of CF(2)FG and CF(2)H radicals has provided a more sustainable alternative to other conventional radical‐triggered reactions from the viewpoint of safety, cost, availability, and “green” chemistry. A wide range of difluoroalkylating reagents has been successfully implemented in these organic transformations in the presence of transition metal complexes or organic photocatalysts. In most cases, upon excitation via visible light irradiation with fluorescent light bulbs or blue light‐emitting diode (LED) lamps, these photocatalysts can act as both reductive and oxidative quenchers, thus enabling the application of electron‐donor or electron‐acceptor difluoroalkylating reagents for the generation of CF(2)FG and CF(2)H radicals. Subsequent radical addition to substrates and additional organic transformations afford the corresponding difluoroalkylated derivatives. The present review describes the distinct strategies for the transition metal‐ and organic‐photocatalyzed difluoroalkylation of a broad range of organic substrates by visible light irradiation reported in the literature since 2014. [Image: see text]